Drama in South African secondary schools meeting the challenges of educational change - Carklin, Michael Larry (Rhodes University, Faculty of Humanities, Department of Drama, 1996)
South Africa is undergoing fundamental transformation at all levels of government and civil society, requiring a firm commitment to redressing the legacy of apartheid and to the development of South Africa's people. Part of this commitment is to undertake research which complements transformation processes, investigating the most appropriate ways to meet the challenges posed by such change. This study examines the potential of drama in the secondary school to meet key educational challenges, motivating strongly for the inclusion of drama as part of the formal curriculum in all schools. Social transformation has been greatly influenced by policy such as the Reconstruction & Development Programme (RDP) and subsequent Government White Papers which identify the need to develop South Africa's human resources as crucial. It is in this light, arid in the context of great disparity that exists across the education spectrum, that learning experiences of high quality must be provided in schools. It is argued that drama, as an lift form and an educational medium, is able to provide such qualitatively sound learning experiences because it is essentially learner-centered, experiential and holistic, offering unique ways of knowing, understanding and gaining insights. However, the classroom drama experience needs careful conceptualisation itself, particularly in view of the fact that life experiences of pupils are characteriseg by multiplicity and diversity within a new era of social and cultural mixing, as well as increased global interaction through, for example, the mass media and the internet. This study thus argues from a post-structuralist perspective, which embraces notions of multiplicity, proposing a reconceptualisation of the classroom drama experience that challenges the oppositional or binary perspectives that have previously characterised the way we think about drama and education. Example~ include art versus utilitarianism; process versus product; drama versus theatre. Investigating the classroom drama experierice in the light of developments in postmodern theatre, this study proposes that classroom drama should be seen as a form of theatre itself and suggests the term theatricalisaction to describe this classroom-theatre process which is based on action, reflection, experience and creative expression. It becomes a theatre of activity or an activating theatre. In this light classroom drama is considered in a specifically South Mrican context. In particular, this study examines the ways in which the following contexts impact upon the drama experience: the education system, the place of the arts within that system, and cultural and linguistic diversity in the classroom. Drawing on policy documentation, conference proceedings and studies that have been carried out in multiculturalism and multilingualism, the specific educational challenges facing South Africans are identified. In further exploring the potential of drama to meeting these challenges, this study documents the results of surveys conducted with drama teachers and with ~students who have studied drama as one of their formal subjects, highlighting in particular their perceptions, perspectives and experiences regarding the aims and value of drama education. Finally, in light of the information gained from teachers and learners, and of the concepts and contexts investigated, this thesis considers the ways in which the drama experience can contribute to meeting three primary educational challenges: the building of a culture of learning; the development and empowerment of pupils; and the embracing of cultural and linguistic diversity. This study concludes that drama is able to contribute significantly to educational change because of the teaching and learning processes it offers as an art form, and in particular, a theatre form. It is such a participatory, democratic classroom-theatre which provides a teaching and learning approach that should be at the core of transformation.
Keywords: Drama in education -- South Africa